2022
DOI: 10.1016/j.mayocp.2021.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Etiology of Cirrhosis and Survival Among Patients Hospitalized in Intensive Care Units

Abstract: Objective: To determine short-term outcomes of patients with alcohol-associated cirrhosis (ALC) admitted to the intensive care unit (ICU) compared with other etiologies of liver disease. In addition, we investigate whether quick sequential organ failure assessment accurately predicts presence of sepsis and in-hospital mortality in critically ill patients with various etiologies of cirrhosis. Methods: A retrospective cohort of 1174 consecutive patients with cirrhosis admitted to the ICU between January of 2006 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…A total of 411 patients presented multiple admissions (28.8% of the investigated group). This result is much lower than the readmission rates reported by various researchers (50-78%), possibly due to the limitation of the patients' accessibility to medical services during the COVID-19 pandemic [19][20][21]. Hepatic encephalopathy (70.6%), ascites (48.6%), and variceal bleeding (32.1%) were the most common causes that led to hospitalization.…”
Section: Discussionmentioning
confidence: 68%
“…A total of 411 patients presented multiple admissions (28.8% of the investigated group). This result is much lower than the readmission rates reported by various researchers (50-78%), possibly due to the limitation of the patients' accessibility to medical services during the COVID-19 pandemic [19][20][21]. Hepatic encephalopathy (70.6%), ascites (48.6%), and variceal bleeding (32.1%) were the most common causes that led to hospitalization.…”
Section: Discussionmentioning
confidence: 68%
“…22 However, other studies have found that the qSOFA score was unable to reliably predict infection, in-hospital mortality, or 30-day mortality. [23][24][25][26] Its performance was found to be inferior to CLIF-SOFA score in a retrospective, multicenter study. 27 The performance of liver-specific models is also lower, with MELD slightly outperforming Child-Pugh.…”
Section: Admissionmentioning
confidence: 92%
“…6 Multiple studies have found admissions for infection to be associated with higher ICU and hospital mortality. 26,29 Some studies have demonstrated that direct admission to the ICU is associated with better prognosis than initial admission to a hepatology unit. 16,30,31 However, not all decompensating events will require ICU monitoring and management, and some patients recover well while managed on the floor.…”
Section: Admissionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alcohol abstinence is the primary treatment strategy for alcohol-related liver cirrhosis and may lead to a shift from decompensated to compensated stage. Cirrhotic patients are advised to abstain from alcohol and smoking, irrespective of etiologies [5,6]. With the improvement of lifestyle, nonalcoholic fatty liver disease (NAFLD), also named metabolic dysfunction-associated fatty liver disease (MAFLD), affects approximately 30% of the global population and has become the predominant cause of liver diseases worldwide.…”
Section: Introductionmentioning
confidence: 99%